Desenvolvimento, crescimento e qualidade de hastes florais de dálias cultivadas a campo - Fernandes, Moara Eliza Siqueira (2023)
The dahlia (Dahlia spp) is a widely cherished ornamental plant in the world of gardening and landscaping. Belonging to the Asteraceae family, it propagates through various techniques, including seeds, cuttings, stems, and tubers. In Rio Grande do Sul, the PhenoGlad Team at the Federal University of Santa Maria leads an important experiment dedicated to understanding the ecophysiology and adaptation of different dahlia cultivars in the subtropical conditions of Brazil. This study, conducted in collaboration with the Brazilian Academy of Floral Artists and a bulb producer in Holambra, São Paulo, is an integral part of the "Flowers for All" Project, an initiative led by the PhenoGlad Team. Since its inception in 2018, the project has achieved remarkable milestones until June 2023, including the involvement of 313 rural families and 53 rural schools in 16 Brazilian states and the Federal District. Its purpose is multifaceted, aiming to transform floriculture into an income alternative for family farmers, promote local production and consumption of flowers, create jobs in the community, rescue low-cost flower species, and encourage youth to stay in rural areas to ensure the continuity of rural families. The overarching goal of the study is to understand and characterize the growth and development of dahlias cultivated in the southern region of Brazil. This becomes even more relevant due to climate change, which is causing rising temperatures and extreme heatwaves. The first article focused on determining the upper lethal temperature that causes irreversible damage to dahlias, concluding that irreversible thermal injuries occur at temperatures above 35°C. This has important implications for farmers, who can adopt practices such as artificial shading and selecting appropriate planting dates to mitigate heat stress. The second article analyzed leaf development during the vegetative phase of dahlias, identifying variations in phyllochron and the final number of leaf pairs in different cultivars. These results provide valuable information for growers, allowing for the optimization of crop growth. The third article explored the growth and development of eleven dahlia cultivars in subtropical conditions in Brazil, taking into account the specific climatic conditions of the region. The results highlighted the significant influence of air temperature on plant development, with notable differences between cultivars and locations. This offers crucial guidance for agricultural planning and the proper selection of cultivars under different conditions. Throughout the study, some cultivars stood out for their adaptability and commercial interest, such as Rebecca's World and Siberia, which also exhibited hardiness characteristics. This research provides a comprehensive understanding of dahlia cultivation, from its response to thermal stress to the selection of ideal cultivars under diverse climatic conditions. These findings are essential to empower farmers to tackle the challenges of climate change and promote sustainable dahlia production in Brazil.